Comparison of Classic Laryngeal Mask Airway and I Gel Regarding Ease of Insertion and Efficacy of Ventilation in Lateral Position - Patel, Viral Prakashkumar; Bayer, Rekha; Patel, Hippal; Patel, Kuntal (Academia Anesthesiologica International, 2019)
Background: The laryngeal mask airway (LMA) is a supraglottic airway device designed to maintain a clear airway, which sits outside of and creates a seal around the larynx. Aim of our study is to compare the ease of insertion and adverse effects using the insertion of classic LMA ad I gel in lateral position and to note if there are any adverse effects between both. Subjects and Methods: Hundred patients of either gender aged between 15 and 70 years who belonged to ASA physical status I and II, who were posted for elective surgical procedures under general anaesthesia under supraglottic airway devices were recruited for study. They were randomly divided into four groups of 25 patients each by closed envelop method. First group is Group IRL: Patients in whom I gel was used in right lateral position Second group is Group ILL : Patients in whom I gel was used in left lateral position Third group is Group CRL : Patients in whom classic laryngeal mask airway was used in right lateral position Fourth group is Group CLL : Patients in whom classic laryngeal mask airway was used in left lateral position. Results: Group IRL had success rate of 88.5% in 1st attempt 11.5% in this group had 2nd attempt of LMA insertion. Group ILL had 1st attempt success rate of 76% with. 24% patients needed 2nd attempt for LMA placement Group, CRL had success rate of 86% at 1st attempt 14% patients had LMA insertion in 2nd attempt. Group CLL had 1st attempt success rate of 67% only. 33% of patients in this group needed 2nd attempt for successful LMA insertion. Conclusion: Supraglottic airway devices can be successfully used for securing airway in lateral position. Both classic LMA and I gel can be used to secure the airway. I gel is a supraglottic airway device with its own advantages which can be successfully used in patients who need lateral position for their surgery.